An interactive problem-posing guiding approach to bridging and facilitating pre- and in-class learning for flipped classrooms. Issue 8 (17th November 2019) - Ye, Xin-Dong; Chang, Yi-Hsin; Lai, Chiu-Lin
ABSTRACT: Educators have indicated that a good flipped learning design has the potential to enable teachers to use the class time effectively for conducting higher-order thinking activities and enhancing the interactions among peers and teachers. Several previous studies have also pointed out the importance of employing proper learning strategies, such that students' learning performance would meet the expectations of both the pre- and in-class activities of flipped learning. In this study, an interactive problem-posing guiding strategy was proposed to guide students to understand the concepts of problem-posing by the use of multiple choice options before class, and to engage them in effective problem-posing activities during class. To examine the effectiveness of the proposed learning mode, a flipped learning system was developed and an experiment was conducted in a natural science learning activity in an elementary school. The participants were two classes of fifth graders of an elementary school, a total of 56 students, with one class as the experimental group and the other as the control group. The students in the experimental group adopted the interactive problem-posing guiding strategy in the flipped learning mode, while the control group used the conventional flipped learning mode. The experimental results confirmed that the flipped learning activity with the interactive problem-posing guiding strategy was more effective in terms of learning achievement, self-efficacy, and deep approaches to learning science in the natural science course than the conventional flipped learning method. It also confirmed the importance of integrating the stepwise learning strategy (e.g. guided problem-posing and collaborative problem-posing) into flipped learning to support students' pre- and in-class learning.